"دراسة بحثية لتأثير استخدام الحصويات البازلتية المحلية على مواصفات الخرسانة المتصلبة " - رياض العيسى; أندرواس سعود; علي محمد (Tishreen University, 2018)
تبحث هذه الورقة دراسة عملية مخبرية لإمكانية الاستفادة من مورد هام من الموارد الطبيعية المتوفرة في القطر، وهو البازلت المتواجد بكميات كبيرة في المنطقة الجنوبية (السويداء)، لبيان مدى تحقيقه لمتطلبات المواصفات القياسية لاستعماله في تصنيع الخرسانة وذلك من خلال اختبار مقاومة الضغط والشد بالانفلاق ومعامل المرونة للخرسانة المتصلبة بأعمار مختلفة (28-7-3) يوم. وفي النتيجة تبين أن اختبارات المقاومة على الضغط ازدادت بنسبة 20% تقريباً مع تقدم عمر الانضاج للخلطات الخرسانية. كما أن المقاومة على الضغط للخلطات الخرسانية المحضرة باستعمال الحصويات البازلتية المدروسة كانت أعلى بنسبة 18 % تقريباً من مقاومة الضغط للخرسانة المصنعة باستعمال الحصويات الكلسية في الأعمار فوق (7) يوم. كما تبين انخفاض طفيف بنسبة 8% في مقاومة الشد بالانفلاق للعينات المحضرة بالحصويات البازلتية المدروسة على العينات المحضرة باستعمال حصويات كلسية وازدياد هذه المقاومة مع الزمن. أما معامل المرونة فقد لوحظ ازدياد معامل المرونة للبيتون بنسبة 20% مع تقدم عمر الإنضاج للخلطات الخرسانية مقارنة بالخلطة المرجعية. This paper studies  a practical laboratory research  of the possibility of utilizing the natural resources available in the country, namely Basalt, which is available  in large quantities in the southern region (Al-Suwayda) in order to demonstrate the extent to which it meets the requirements of  standard specifications for use in the manufacture of (Reinforced) concrete by means of  testing the resistance of pressure and tensile by splitting  and the elasticity coefficient of hardened (rigid concrete)  at  Different  ages (3-7-28) days. As a result, pressure resistance tests increased by approximately 20 % with the maturating period progress of concrete mixtures. The pressure resistance of concrete mixtures prepared using basalt pebbles  was approximately 18% higher than the pressure resistance of concrete formed usingcalcite(calcareous) pebbles in ages above 7 days There was also a slight decrease of 8% in the split tensile resistance of the studied samples prepared with basalt minerals  , compared with the samples prepared using calcite (calcareous)  pebble and this resistance increases over time . As for the elasticity coefficient , a  20% increase in the elasticity coefficient of the concrete was noticed with  the maturating of the concrete mixtures compared to the referential  mixture.